Are circumcised men safer sex partners?: findings from the HAALSI cohort in rural South Africa - Rosenberg, Molly S.; Bärnighausen, Till (PLOS ONE, 2018)
Introduction: The real-world association between male circumcision and HIV status has important implications for policy and intervention practice. For instance, women may assume that circumcised men are safer sex partners than non-circumcised men and adjust sexual partnering and behavior according to these beliefs. Voluntary medical male circumcision (VMMC) is highly efficacious in preventing HIV acquisition in men and this biological efficacy should lead to a negative association between circumcision and HIV. However, behavioral factors such as differential selection into circumcision based on current HIV status or factors associated with future HIV status could reverse the association. Here, we examine how HIV prevalence differs by circumcision status in older adult men in a rural South African community, a non-experimental setting in a time of expanding VMMC access. Methods: We analyzed data collected from a population-based sample of 2345 men aged 40 years and older in a rural community served by the Agincourt Health and socio-Demographic Surveillance System site in Mpumalanga province, South Africa. We describe circumcision prevalence and estimate the association between circumcision and laboratory-confirmed HIV status with log-binomial regression models. Results: One quarter of older men reported circumcision, with slightly more initiation-based circumcisions (56%) than hospital-based circumcisions (44%). Overall, the evidence did not suggest differences in HIV prevalence between circumcised and uncircumcised men; however, those who reported hospital-based circumcision were more likely to test HIV-positive [PR (95% CI): 1.28 (1.03, 1.59)] while those who reported initiation-based circumcision were less likely to test HIV-positive [PR (95% CI): 0.68 (0.51, 0.90)]. Effects were attenuated, but not reversed after adjustment for key covariates. Conclusions: Medically circumcised older men in a rural South African community had higher HIV prevalence than uncircumcised men, suggesting that the effect of selection into circumcision may be stronger than the biological efficacy of circumcision in preventing HIV acquisition. The impression given from circumcision policy and dissemination of prior trial findings that those who are circumcised are safer sex partners may be incorrect in this age group and needs to be countered by interventions, such as educational campaigns.